The e-service quality of e-commerce websites: what do customers look for?/ Sabiroh Md Sabri... [et al.] - Md Sabri, Sabiroh; Annuar, Nursyamilah; Abdull Rahman, Nurul Labanihuda; Syed Abdul Mutalib, Sharifah Khairol Musairah; Abd Mutalib, Hasyeilla; Subagja, Iwan Kurniawan (Universiti Teknologi MARA, Perlis, 2022)
The introduction of information technology has changed the way people deal with businesses especially when buying products. People can select and buy their desired products at any time and anywhere using an e-commerce website. They can easily pay using credit cards or mobile payment options on the e-commerce website. The e-commerce website plays a vital role in determining customer satisfaction and loyalty to a business. However, e-commerce developers face difficulties with the features of e-commerce websites. The features impact the e-commerce business greatly where it should satisfy the customers' needs. To gain a better understanding of this, this research was carried out to identify the components of e-service quality in the e-commerce business and develop an e-service quality model for e-commerce websites. This research was conducted using the qualitative method through a semi-structured interview. The research result presents the findings from the interview session with eight customers who have experience in purchasing products or services through the e-commerce business. Nine components of e-service quality have been identified which are fulfilment, responsiveness, availability, ease of use, assurance, website design, credibility, reliability, and accessibility. The results obtained from this research could be used by the e-commerce website developer to recognize the areas of improvement and components of e-service quality in the e-commerce business. This research also benefits by contributing to a general knowledge of the e-service quality field and enhances the future understanding of e-service quality components in the e-commerce business.